How language teachers perceive information and communication technology - Djiwandono, Patrisius Istiarto (Indonesian Journal of Applied Linguistics, 2019)
The digital technology has permeated almost every aspect of life. Meanwhile, the responses from the field of language teaching in Indonesia to this new development have been scarce. The paper aims to provide an answer to the question whether language teachers perceive Information and Communication Technology (ICT) as a threat or a helpful assistant. To achieve this, a survey was conducted to 110 English teachers in Java, Indonesia. Five closed-ended items and two open-ended items in an online questionnaire asked them several questions about what conditions they see as threats, how they perceive ICT, and what digital facilities they have been using in their work. The results show that most of them perceived ICT positively, seeing it as a beneficial rather than threatening force. To them, ICT has been an attractive source that provides learning resources, fosters communication and collaboration, and spices up teaching-learning activities. Those who expressed their worry over ICT mentioned the importance of teachers’ upgrading their ICT skills and called for institutional support for the teachers. Three models, TAM (Technological Acceptance Model), UTAUT (Unified Theory of Acceptance and Use of Technology), and TPACK (Technological Pedagogical Content Knowledge) were then discussed to address the need for helping teachers adapt to the fast-changing digital technology.